Desire For Wealth In Theodore Dreiser's Novel Sister Carrie (1900): A Psychoanalytic Approach - Nusagam, Andamruci Nonika (2012)
The major problem of this study is how the desire for wealth is reflected in the major character's personality. The aim of this study is to analyze Theodore Dreiser's Sister Carrie novel based on the structural elements and the development of personality of the major character based on Psychoanalytic Perspective. This study focuses on the major characters, namely Carrie. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the novel itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is is library research by collecting and selecting both primary and secondary data, while the technique of Data Analysis in this study is descriptive. Based on the structural analysis it is evident that in this novel, Theodore Dreiser wants to deliver a message that wealth does not always give happiness. Based on the psychological analysis, it is clear that in Sister Carrie novel Dreiser describes a psychological phenomenon, in which the major characters, Carrie is obsessed by the desire for wealth. Carrie who has strong desire for wealth may do bad things until she gets what she wants.